The restructuring process of the Samancor Manganese Mines (May 2000-June 2001) / C.L. Steenkamp - Steenkamp, Chantal Lynne (North-West University, 2009)
In terms of remaining profitable, being competitive and keeping up with technological advances, change is a familiar occurrence in the global business environment. From a business perspective, changes can take place because of, for example, new products on the market, competition, mergers of companies, different needs of clients and hostile take-overs. In order to survive and remain profitable in this dynamic business environment, companies must be able to adapt. In many cases, adaptation entails the restructuring of the company. Restructuring can coincide with, for example, the flattening of the organisational structure of a company, measures to become more cost effective and the acquisition of a larger share of the market. It is therefore required of any company to have an effective plan in place when change in the internal and external environments necessitates restructuring. Elements of restructuring are: effective planning; communication; management and leadership. At Samancor Manganese Mines (now known as Hotazel Manganese Mines), a restructuring process took place as a result of an international merger between Broken Hill Productions (BHP) and Billiton International (the company is now known as BHP Billiton International). As a sub division of the former Billiton International, Samancor Manganese Mines had to restructure in order to remain profitable and become more cost effective. In terms of these criteria, it is accepted that the restructuring process was successful. The flattening of the organisational structure of the mine, however, led to mass retrenchments that resulted in the low morale of employees. Although the whole process of restructuring was a legitimate and familiar business practice, the basic assumption of this research is that the restructuring strategy should have been communicated differently to employees. If communicated timely and effectively, the restructuring process would have been less painful. In this regard, the research intends to firstly analyse and describe a restructuring process; secondly compare that process with the process that took place at Samancor Manganese Mines; and thirdly make recommendations in regards to how the restructuring process at Samancor Manganese Mines should have been managed, with specific reference to communication from the perspective of employees. === Thesis (M. Ontwikkeling en Bestuur)--North-West University, Potchefstroom Campus, 2004.